Sustainable thermo-acoustical insulation material from cardboard waste and natural fibers: Elaboration and performance evaluation. (November 2022) - Ouakarrouch, Mohamed; Laaroussi, Najma; Garoum, Mohammed; Bousshine, Said; Bybi, Abdelmajid; benallel, Abderrahim; Tilioua, Amine
The main objective of this paper is to elaborate and characterize new ecological composites based on cardboard waste and abandoned natural fibers, in the Drâa-Tafilalet region (South-East, Morocco), for the manufacture of local thermo-acoustical insulation panels. For this study, 25 samples were prepared by mixing 60% of cardboard waste and 40% of vegetable fibers (Reed tree, esparto fiber, fig tree, and Olive tree). The morphological analysis of the different fibers was carried out by scanning electron microscopy (SEM), while, the physical, thermal, and acoustical properties of samples were measured experimentally using standard methods. The experimental results showed that all new composites have better thermal and acoustical performances comparable to those of synthetic insulation materials. The density, thermal conductivity, thermal diffusivity, and sound absorption coefficient of those composites were in the range of 278.6–343.8 kg/m 3 ; 0.072–0.10 W/m·K; 1254.5–1807.5 J/kg·K; 0.4–0.8, respectively. Consequently, the by-products recovered in this study are good candidates for the development of local insulation materials with useful properties for thermal and acoustical insulation applications in buildings, low environmental impact, low cost, and competition with commercialized synthetic insulation materials.